WIND SPEED ON ULTRA HIGH FREQUENCY (UHF) OF RADIO SIGNAL - Roslan, Umar; S. N. A. Syed, Zafar; S. N., Hazmin (2018)
East coast of Peninsular Malaysia has received average wind speed up to 55km/h which equivalent to 15.4m per second and 30 knot, especially during monsoon. These circumstances had affected the radio signal by degrading its strength and quality. This study observe the relationship of wind speed and radio signal in Ultra High Frequency band. The statistical spearman correlation were applied and graph relationship of two variables were plotted in order to investigate these two variables. The measurement were done at 24 hour in February and July 2016 at Kusza Observatory. Analysis of result shown that high correlation strength (r = 0.555) was indicated in first of observation (1-O) at frequency of 382.5MHz. No high correlation were quantified in second of observation (2-O). These findings related to the observed high wind speed which is brought high of water vapor, hence attenuating the radio signal